1996
DOI: 10.1046/j.1365-2427.1996.d01-508.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing by a native and an exotic crayfish on aquatic macrophytes

Abstract: 1. We compared grazing by native noble crayfish (Astacus astacus) and the exotic signal crayfish (Pacifastacus leniusculus) on seedling or well‐established macrophytes. 2. In a pool experiment, seedlings of emergent Scirpuslacustris and floating‐leaved Potamogetonnatans were heavily grazed by adult signal crayfish, whereas established plants of the same species sustained only minor damage. 3. In a preference experiment two submerged macrophytes (Charavulgaris and Elodeacanadensis), and both seedlings and estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 2 publications
8
92
0
3
Order By: Relevance
“…Presence of crayfish of Astacus sp. has been associated with reduction in submerged macrophytes (Nyström and Strand, 1996;Nyström et al, 1999), reduced biomass of grazers, particularly gastropods, and shifts in community composition towards predatory invertebrates (Nyström et al, 1999). Some crayfish species are also significant bioturbators, modifying sediment transport and increasing turbidity (Harvey et al, 2011;Johnson et al, 2011), with indirect effects on algae and macrophyte cover (Dorn and Wojdak, 2004;Usio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Presence of crayfish of Astacus sp. has been associated with reduction in submerged macrophytes (Nyström and Strand, 1996;Nyström et al, 1999), reduced biomass of grazers, particularly gastropods, and shifts in community composition towards predatory invertebrates (Nyström et al, 1999). Some crayfish species are also significant bioturbators, modifying sediment transport and increasing turbidity (Harvey et al, 2011;Johnson et al, 2011), with indirect effects on algae and macrophyte cover (Dorn and Wojdak, 2004;Usio et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Through a combination of large size, broad feeding habitats and high densities attained, their introduction to new habitats can have a significant impact on the aquatic environment (NYSTRÖM and STRAND, 1996;NYSTRÖM, 2002;DORN and WOJDAK, 2004). The introduction of North American crayfish species into Europe has been partially responsible for severe declines in indigenous European species (HENTTONEN and HUNER, 1999;HOLDICH, ROGERS and REYNOLDS, 1999) through a combination of transfer of crayfish plague Aphanomyces astaci and competitive displacement of native European species.…”
Section: Introductionmentioning
confidence: 99%
“…High populations and activity of signal crayfish may have negative impacts on resident fish. Signals directly predate on small fish such as stone loach and bullhead (Guan and Wiles, 1997), and on fish fry (Rubin and Svensson, 1993), while alteration of invertebrate communities (Crawford et al, 2006) and cropping of macrophytes by crayfish may put themselves and other denizens at risk (Lodge and Lorman, 1987;Hart, 1993, 1995;Matthews et al, 1993;Nyström and Strand, 1995). Studies have shown that predatory fish interfere with crayfish survival, activity and food consumption, e.g.…”
Section: > Signal Crayfish Pacifastacus Leniusculusmentioning
confidence: 99%